Providers' perspectives on substance use among solid organ transplant candidates in a pediatric hospital. (11th February 2020) - Steinberg Christofferson, Elizabeth; Burgers, Darcy E.; Buchanan, Cindy; Suplee, Amanda F.; Upshaw, Naadira; Ariefdjohan, Merlin
Abstract: Introduction: Substance use is prevalent among youth and often leads to impairment in multiple domains. Additionally, substance use may pose adverse health issues post‐transplant. Yet, practices related to substance use among pediatric patients who require organ transplant remain inconsistent. In this study, providers were surveyed for their perspectives on substance use among solid organ transplant candidates within a pediatric hospital. Methods: An online survey was administered to providers on the heart, kidney, and liver transplant teams at one tertiary pediatric care center located in the intermountain region of the United States (N = 50, 42% response rate). Providers answered questions about the need for a hospital‐wide policy across heart, liver, and kidney transplant teams within this transplant center, timing of substance use evaluation, types of substances eliciting concerns based on organ, and recommended interventions. Data were analyzed using descriptive statistics. Results: Providers felt strongly about the need for a policy to guide recommendations for substance use among transplant candidates. Providers wanted a hospital‐wide substance use policy (84%) and a standardized measure for assessing substance use (98%). Respondents (98%) indicated that substance use should be assessed during the pretransplant evaluation. Respondents expressed varied concerns based on substance and organ type, and recommended interventions for patients to cease substance use prior to transplant listing. Conclusions: This study highlights the need for a clear, directive, hospital‐wide policy and standardized procedure for evaluating substance use among adolescent solid organ transplant candidates nationally across pediatric transplant centers.